(untitled) (Economic and Political Thought, 2013)
The article presents the operations of the Polish pension schemes. The most important ones are the open pension schemes (OFE); they are one of the key factors of the economic development in Poland. Their role is especially evident on the capital market. The participation in the schemes is obligatory. Their growing size and massive financial operations cause that the success of privatization of public sector companies, the situation at the stock exchange and the cost of the issue of bonds to a large extend depend on them at present. The role of optional pension schemes has been much lower so far; their importance will definitely rise in the future.